Alkaline Phosphatase is not Associated with Insulin Resistance: A Retrospective Cross-Sectional Study - (:unkn) unknown (MODESTUM LTD, 2020)
Background: Many epidemiologic studies suggested that vitamin D deficiency is associated with obesity but the relationship between obesity and alkaline phosphatase (ALP) is controversial. In this study association between insulin resistance and alkaline phosphatase is investigated. Methods: Of the 124 women aged (35,942 9,714) years with (39,47 7,66) body mass index (BMI) and with vitamin D deficiency is included. The relationship among insulin, glucose, parathormone (PTH), calcium (Ca), alkaline phosphatase (ALP) were evaulated with correlation, linear regression and ANOVA (with post hoc TUKEY). Statistical analysis performed with Eviews v.11 and Graphpad Prism v.8.1 Results: There was no significant correlation among Vitamin D, ALP and PTH in non-insulin resistance patients. A weak correlation was found among Vitamin D, ALP and Parathormone in insulin resistance group. There was no significant elevation between ALP levels in patients with or without insulin resistance. Conclusion: Elevation in ALP levels is not associated with insulin resistance. It might be a response to elevated parathormone levels. Further investigations in large populations are required to understand the relationship between insulin resistance and ALP.
Keywords: alkaline phosphatase; insulin resistance; parathormone; vitamin D; VITAMIN-D DEFICIENCY; LIVER-ENZYMES; DISEASE; MARKER